CONTEXTUAL TRAINING MODEL IN THE PRACTICAL COURSE OF GENERAL TECHNICAL DISCIPLINES - Natal'ja N. Jel'jash (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is a verification of new model necessity of vocational training within the graduates of technical branches of study in high schools. Expert's activity unlike educational activity is not structured-indetail. Knowledge from the diversified areas and based on it skills to find out appropriate, uncommon decisions of current problems and arising problems are required for effective work on present-day production with constantly improved and becoming complicated technologies. The traditional reproductive training focused on presentation of a set of information and given algorithms for completing different activities presented by the teacher does not allow forming properly creative research way of thinking, abilities to master professional innovations and readiness for regular self-education of trainees. The author notes that it is necessary to work out and introduce essentially alternate methods of preparation that would provide systematic integrity of the systematised theoretical knowledge with acquirable practical skills and its application. The author considers the contextual model of training as one of the most appropriate and reasoned. Methods. The core theory of contextual training is the statute of sensemaking influence of professional work context on educational activity of the student. Theoretically training is to be carried out in the closest field and in forms to real activity; as a peculiar kind of immersion to the future professional sphere. The proposed model of contextual training is installed on the basis of activity approach. The activity approach in contrast to traditional system preparation isn't broken up to two stages (firstly, overlearning, then its practical application), but is posed to be indivisible: mastery to theoretical readiness and required practical skills acquisition refer a concurrent process under the performance of any tutorial activity or task at the training subject. Results. The principles of contextual training model are pointed out. The performance technique of the practical tasks which logic is close to logic of real professional work is considered. Scientific novelty. The novelty of contextual training model in relation to designing of academic and didactic materials consists in updating of practical training, corresponding coherence of theory and practice as the essential formation of professional skill and competency. The solution algorithms under the reduced or formerly known formula and functional connections are organized in such a way as to motivate the student for regular appeal to educational sources of information (such as textbooks, study guides, reference books). The author states that the uselessness and unreliability perception of theory mastering is avoided due to the proposed training; problem solving is not confined to simple mathematical calculations. Physical sense of conception and phenomenon essence occurs while performing the task. Practical significance. The research outcomes can be used while academic teaching packages designing and its implementation into educational process of high school. The research findings can help to form sustained professional competencies, students' interest upgrading to studied disciplines, establishment of intersubject communication between the training courses provided by educational program.